El cultivo de las Ciencias Humanas en el Centro de Estudios Históricos de la JAE - López-ocón Cabrera, Leoncio (Revista Complutense de Educación, 2007)
The Centro de Estudios Históricos was the first institution created by the Junta para Ampliación de Estudios e Investigaciones Científicas (JAE) with the aim to spread out the knowlegment of the past of the hispanic society.It played a very special role in the renovation and development of historiographic methods, and in the configuration of a spanish school of Filology leaded by Ramón Menéndez Pidal. Other remarkable researchers were Américo Castro and Tomás Navarro Tomás. But the Centro de Estudios Históricos was not only a set of laboratories for the study of human and social sciences. The activities of this institution also promoted the educational innovation by the organisation of seminars, or courses of Spanish for foreigners.